Gender imbalance and risk factor interactions in heparin-induced thrombocytopenia - Warkentin, Theodore E; Sheppard, Jo-Ann I; Sigouin, Christopher S; Kohlmann, Thomas; Eichler, Petra; Greinacher, Andreas (Blood, 2006)
Heparin-induced thrombocytopenia (HIT) is caused by antibodies against a "self" protein-platelet factor 4-bound to heparin. We observed an overrepresentation of the female gender in 290 patients who developed HIT after cardiac or orthopedic surgery compared with the representation found in national databases (study 1). Therefore, we investigated gender imbalance in HIT by logistic regression analysis of a randomized controlled trial of unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) (study 2), and we analyzed individual patient data from 7 prospective studies comparing HIT frequency between UFH and LMWH, evaluating effects of gender, heparin (UFH vs LMWH), and patient type (surgical vs medical) (study 3). All 3 studies showed female overrepresentation, which for study 3 was a common odds ratio (OR) of 2.37 (95% confidence interval [95% CI], 1.37-4.09; P = .0015). Study 3 also showed an interaction between gender, heparin, and patient type. Although UFH was more likely than LMWH to cause HIT (P < .0001), this effect was predominantly seen in women compared with men (common OR, 9.22 vs 1.83; P = .020) and in surgical patients compared with medical patients (common OR, 13.93 vs 1.75; P = .005). We conclude that females are at greater risk for HIT and that using LMWH to prevent HIT may have greatest absolute benefit in females undergoing surgical thromboprophylaxis.